SEJARAH MATEMATIKA PADA ZAMAN MESIR DAN BABILONIA - Indah Ayu Wulandari; Muhammad Budiyono; Abdulah Abdulah (UNEJ e-Proceeding, 2022)
This article examines Egyptian and Babylonian computing systems. To explore Egyptian and Babylonian geometry, Egyptian computations. The Egyptians developed two different number systems, one for each of their two writings. In the hieroglyphic system, each of the first few powers of 10 is represented by a different symbols, starting with the familiar vertical stroke for 1. The Hieroglyphic Number System In so-called "hieratic" (sacred) scripts, the symbols are written in cursive, or running freely, hands so that at first glance the shapes are not very similar with old hieroglyphs. Through literature study research to get an analysis of the history of mathematics in Egypt and Babylon. Keywords: Babylon, Mathematics, Egypt, History